2018
DOI: 10.1186/s12978-018-0464-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of the client-provider ratio with the risk of maternal mortality in referral hospitals: a multi-site study in Nigeria

Abstract: BackgroundThe paucity of human resources for health buoyed by excessive workloads has been identified as being responsible for poor quality obstetric care, which leads to high maternal mortality in Nigeria. While there is anecdotal and qualitative research to support this observation, limited quantitative studies have been conducted to test the association between the number and density of human resources and risk of maternal mortality. This study aims to investigate the association between client-provider rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Consistent with our findings, the CPED revealed that primary healthcare settings in rural areas are disproportionately lacking in both equipment and human resources. Maternal deaths have been shown to decrease significantly when women were treated by diverse healthcare personnel [58].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, the CPED revealed that primary healthcare settings in rural areas are disproportionately lacking in both equipment and human resources. Maternal deaths have been shown to decrease significantly when women were treated by diverse healthcare personnel [58].…”
Section: Discussionmentioning
confidence: 99%
“…This is, unfortunately, not the case in Nigeria due to an inequitable distribution and shortage of appropriate cadres of health workers. 4 Strategies to effectively address gaps in HRH hiring, deployment, and retention, at national and state levels, are needed to optimize FLHWs-their quality, quantity, distribution, and skills-in Nigeria. Little is known about the documentation and implementation of policies and processes for FLHW hiring, deployment, and retention, and important contextual factors, particularly in Cross River and Bauchi, are poorly understood.…”
Section: Justification For the Studymentioning
confidence: 99%
“…There is insufficient availability of skilled health workers in Nigeria due not only to shortages but inequitable distribution of appropriate health workforce cadres in favor of urban areas. 4 Nigeria's Federal Ministry of Health (FMoH) developed a comprehensive National HRH Policy (2006) as well as national HRH strategic plans (2008)(2009)(2010)(2011)(2012)(2009)(2010)(2011)(2012)(2013)(2014)(2015) to guide HRH policy and response with renewed focus on comprehensive and integrated HRH management. 5,6 The framework of the National Strategic Health Development Plan (NSHDP, 2010-2015) provided a better coordinated health sector response to HRH needs such as availability and equitable distribution of a skilled and well-motivated health workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial formative research in eight referral hospitals in four geo-political zones of the country identified several factors that were perceived by women and health providers as associated with poor quality antenatal, delivery and postnatal care in the hospitals. These included 1) the lack of official commitment to quality care [ 16 ];2) limited ‘providers’ skills and knowledge [ 17 ]; 3) long waiting hours in the antenatal clinics [ 18 ]; 4) abusive care by providers and poor ancillary services [ 19 ], and 5) heavy provider workloads [ 20 ].…”
Section: Introductionmentioning
confidence: 99%